2022
DOI: 10.3390/metabo12060554
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism Is Dysregulated in the Motor Cortex White Matter in Amyotrophic Lateral Sclerosis

Abstract: Lipid metabolism is profoundly dysregulated in amyotrophic lateral sclerosis (ALS), yet the lipid composition of the white matter, where the myelinated axons of motor neurons are located, remains uncharacterised. We aimed to comprehensively characterise how myelin is altered in ALS by assessing its lipid and protein composition. We isolated white matter from the motor cortex from post-mortem tissue of ALS patients (n = 8 sporadic ALS cases and n = 6 familial ALS cases) and age- and sex-matched controls (n = 8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Levels and distributions of lipid metabolites are indicators of lipid metabolism [ 1 , 2 , 26 , 27 ]. MALDI-TOF MS results demonstrated that glycerophospholipids such as DG, PA, PE, and PC were significantly increased in Seipin KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Levels and distributions of lipid metabolites are indicators of lipid metabolism [ 1 , 2 , 26 , 27 ]. MALDI-TOF MS results demonstrated that glycerophospholipids such as DG, PA, PE, and PC were significantly increased in Seipin KO mice.…”
Section: Discussionmentioning
confidence: 99%